Typical procedural nullities of Art. 564 of the CPP: a study in the light of jurisprudences of the STF and STJ (2011-2021) (Research, Society and Development, 2022)
The present study has the general objective of presenting a survey of jurisprudence of the STF and STJ that address the nullities provided for in Art. 564, of the CPP, classifying them into absolute and/or relative. 44 (forty-four) judgments of the STJ and 07 (seven) of the STF were raised, totaling 51 (fifty-one) decisions. The decisions selected for the present study did not reach all the cases listed by Art. 564, of the CPP, were associated with items I, III (items b, c, d, e, g, j, k and o) and IV. in honor of the principle of pas de nullité sans grief (Art. 563, CPP). However, given the range of concrete situations capable of subsuming the provisions of Art. 564 of the CPP, it is not possible to establish rigid a priori classifications, since the categorizations already present in the CPP are sometimes interpreted differently in the scope of doctrine and jurisprudence.